Análisis de las causas de escoliosis en los trabajadores del área de Cross Docking de Servientrega S.A. sede Las Vegas de la ciudad de Medellín, año 2014 (2015)
Scoliosis is a spinal column deformation where a curvature is formed on the coronal plane that exceeds 10 degrees; this curvature can be generated in "S" or "C", its classification may be functional or structural. The objective of this work is to identify what are the causes that produce scoliosis in the workers of Cross Docking area at Servientrega SA, headquarters Las Vegas in 2014, for which the application of OWAS method for doing an ergonomic analysis about positions taken during their work day; besides a physiotherapist assessment was done that included height, weight, body mass index, semiological tests for scoliosis, lower limb shortening, general posture, column strength and prevalent places in whose goods is loaded. This analysis allowed to give information about what was the most prevalent cause for generating scoliosis Cross Docking workers, and according to the results was necessary to provide preventive actions against inappropriate activities found during the analysis time.